2019
DOI: 10.1016/j.molcel.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 and Caspase-8 Ensure Chromosome Stability Independently of Their Role in Cell Death and Inflammation

Abstract: Summary Receptor-interacting protein kinase (RIPK) 1 functions as a key mediator of tissue homeostasis via formation of Caspase-8 activating ripoptosome complexes, positively and negatively regulating apoptosis, necroptosis, and inflammation. Here, we report an unanticipated cell-death- and inflammation-independent function of RIPK1 and Caspase-8, promoting faithful chromosome alignment in mitosis and thereby ensuring genome stability. We find that ripoptosome complexes progressively form as cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…A recent study in models of non-small-cell lung cancer and pancreatic ductal adenocarcinoma interestingly indicates that cancer cells might become addicted to TRAIL receptor expression, with autonomous TRAIL-R signalling contributing to disease progression [1]. Additionally, proliferating cells might rely on a cell death-independent role of caspase-8 in contributing to chromosome alignment during mitosis [46]. In the predictor, the expression of XIAP and caspase-3 strongly contributed to accurate response predictions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in models of non-small-cell lung cancer and pancreatic ductal adenocarcinoma interestingly indicates that cancer cells might become addicted to TRAIL receptor expression, with autonomous TRAIL-R signalling contributing to disease progression [1]. Additionally, proliferating cells might rely on a cell death-independent role of caspase-8 in contributing to chromosome alignment during mitosis [46]. In the predictor, the expression of XIAP and caspase-3 strongly contributed to accurate response predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death-independent functions of Casp-8 have been shown to be both activity dependent (16,64) and independent (acting as a scaffold protein (14,32)). While we do not rule out that Casp-8 could also act as a scaffold protein to regulate the angiogenic response of ECs, here we show that its activity is required.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, VE-cadherin stability was altered at the back of the retina of Casp-8 ECko EC pups, suggesting that EC-EC contacts fail to stabilize. Recent studies indicate that rather than its sole presence or 16 absence (35)(36)(37)39), it is the dynamic and heterogeneous expression of VE-cadherin in different areas of the developing vessel sprout that drives angiogenesis (38). Consistent with this current view, which suggests that EC junctions in the back of the retina have to be stabilized in order to allow proper sprout elongation in the front, we postulate that the increased number of vessel patches with serrated junctions in the back of Casp-8 ECko retinas blocks EC positional interchanges, ultimately resulting in a reduced number of sprouts at the vascular front and thus reduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2E). Intriguingly, recent studies revealed that the nonapoptotic activity of the caspase-8/RIPK1 complex regulates the function of Polo-like Kinase 1, and that loss of either caspase-8 or RIPK1 activity was associated with defects in chromosome segregation, mitotic spindle assembly, and genomic integrity in dividing cells (47). These data indicate that the nonapoptotic activity of caspase-8 has broader cellular functions beyond the control of inflammatory gene expression.…”
Section: Caspase-8 Catalytic Activity Regulates Activation Of the Ikkmentioning
confidence: 93%